A Rare Case of a Lost Suture Needle during Third Molar Surgery - VAROL, ALTAN; GÖÇMEN, GÖKHAN; GÖNÜL, ONUR (HINDAWI LTD, 2015)
The authors report a case that is started with a simple upper third molar's surgical extraction and a broken 3.0 suture needle tip incident occurred. Broken fragment's localization has been detected with 3D cone beamcomputed tomography (CBCT). Needle tip has been reached with the help of CBCT vision. CBCT's benefits have been discussed on these types of cases and further migration of the needle tip during surgical procedure is reported.